Uma colônia no Brasil de Marie Van Langendonck: um relato de viagem sob o olhar de uma estrangeira - Fachinelli, Pamela Pinto Chiareli (2014)
It‟s presents The book Uma Colônia no Brasil that is almost unknown in the academy. It was written by a belgium, Madame van Langendonck and has the purpose of describing her experiences in the Brazilian lands in the period she lived in a colony located in the south of the country, in the years 1857 to 1859. At sixty, Marie van Langendonck boards in an emigrant ship seduced by the desire of living in a virgin forest in Brazil. As soon as we believe the traveler had assimilated the edenic vision of a virgin world relived in the Romantic period, we intend, at first, clarify all the imaginary constructed in letters and in the travel literature in the course of XVI, XVII and XVIII centuries to realize the founding principles that attracted Marie to the unknown and the romantic vision of a virgin world revealed on her preference of living in a cottage in the middle of the forest. While Marie presents a not attractive pioneering life, she makes a negative point of view about the colonization process, so, her judgments are intrinsically related to the elements that figure the Brazilian society after the independence the settler, the native, the slaver and the woman. Therefore, we are going to seek to highlight how her judgments and prejudices about people and politics translate the European vision of sovereignty over the dominated people. Thinking about this involves all the principles that originate how to look the others. In addition, when the book was published in Belgium, instead the subtitles Historical reports, it was considered a diary, however, as we researched on the genre, some theoretical issues were raised, since the story of Marie extrapolates capital characteristics indicated by Blanchot and Lejeune about the diary. This way, we intend to reveal how the memory reconstruction of Marie van Langendonck converges to a particular an attitude of writing, which goes beyond the notions of genre, as a result the autobiographical space of the work is intrinsically linked to the condition of Marie as a woman writer, narrator and character in a society marked by innumerable prejudices, which delimited the role of women.